2016
DOI: 10.1111/ijd.13229
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in dermatologic and dermatopathologic diagnoses: a retrospective 15‐year analysis of dermatopathologic data

Abstract: This study found statistically significant seasonal trends for several dermatologic conditions. The study was primarily epidemiologic and was not intended to address histopathologic differences that might underlie the seasonal variations observed. However, further investigation of seasonal differences in the histopathology of erythema multiforme may prove interesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Clinical observations pointed to the same pattern in psoriasis with deterioration or first episodes starting mainly in cold months [12][13][14]. This pattern was not however observed by all authors, citing multifactorial nature of the disease [15,16]. Recently, a review on seasonal variation of psoriasis in Northern and Central Europe revealed that 50% of patients showed no difference in the severity of their…”
Section: Introductionmentioning
confidence: 85%
“…Clinical observations pointed to the same pattern in psoriasis with deterioration or first episodes starting mainly in cold months [12][13][14]. This pattern was not however observed by all authors, citing multifactorial nature of the disease [15,16]. Recently, a review on seasonal variation of psoriasis in Northern and Central Europe revealed that 50% of patients showed no difference in the severity of their…”
Section: Introductionmentioning
confidence: 85%
“…[ 11 ] While countries with tropical and subtropical climatic conditions (Taiwan, Singapore, Malaysia) had two peaks in a year, those with higher latitudes (South Korea, Japan, Finland, United States) showed a single yearly peak of the disease. [ 7 9 70 71 72 73 74 75 ] Similarly, Finland generally had experienced peaks in early autumn. [ 71 ] We also noted almost similar epidemiological trends for major outbreaks during summers and rainy seasons (April to September), and small outbreaks during autumn (October-November) and winter (December-January) months over these years across India having varied topography, geography and climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although most commonly found in the Central and South American population, ashy dermatosis demonstrates a worldwide prevalence [2][3][4][5]. Ashy dermatosis can appear at any season of the year in patients of any age group or gender [2,6]. Although primarily a cosmetic issue, its prevalence and prominent appearance in dark skinned individuals can be very troubling for patients.…”
Section: Introductionmentioning
confidence: 99%